Analisis Faktor-Faktor yang Berhubungan dengan Bakteriologi pada DAMIU di Wilayah Kerja Dinas Kesehatan Kabupaten OKU - S.B. Nila Sri Dewi; Erma Gustina; Maria Ulfah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
One of the main needs of humans is drinking water. drinking water must meet the requirements both in terms of quantity and quality. The most important aspect to fulfill is the quality aspect, where drinking water can directly affect public health. This study aims to determine the factors related to bacteriology in DAMIU in the Work Area of the Ogan Komering Ulu District Health Office in 2021. The research design used was cross-sectional. This research was conducted in the area of the Health Office of Ogan Komering Ulu Regency in June - July 2021. The population in this study was all DAMIU in the Work Area of the Health Office of Ogan Komering Ulu Regency with a sample of 60 DAMIU. This study shows that there is bacteriological quality in DAMIU, there are 63.3% positive and 36.7% negative. Based on bivariate analysis, it was found that there was a relationship between the condition of the DAMIU processing process (p value = 0.000) and the bacteriological quality of DAMIU. The results of multivariate analysis showed no significant variables with bacteriological quality in DAMIU. The conclusion from these results, that there is a relationship with the bacteriological quality of DAMIU that meets the requirements is the DAMIU processing process (p value = 0.000) and what has no relationship is the condition of the DAMIU source (p value = 0.059), the condition of the DAMIU equipment (p value = 0.185), DAMIU worker hygiene condition (p value = 0.284), DAMIU place condition (p value = 0.691). This study suggests that the Health Office of Ogan Komering Ulu Regency can increase knowledge by way of counseling and public health seminars, especially about the bacteriological quality of DAMIU that meets the requirements of physics, chemistry and microbiology.